Mengembangkan Teori Keynesian untuk Menghadapi Tantangan Ekonomi Masa Depan - Linda Fatmawati; Angga Rosidin; Zakaria Habib Al-Ra’zie (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The current global economic situation is facing various complex challenges, including climate change, economic inequality, and technological revolution. The Keynesian theory, which emphasizes the active role of government in stabilizing the economy, remains relevant for designing adaptive and sustainable economic policies. This article discusses the development of Keynesian theory in addressing future challenges, focusing on green investment, equitable redistribution policies, and strengthening technological innovation. The research method used is a descriptive qualitative literature study with thematic analysis of national and international scientific sources. The findings indicate that the renewal of Keynesian theory should not only aim at maintaining short-term stability but also support long-term sustainability by emphasizing the synergy between fiscal policy, technological innovation, and social justice.